2016
DOI: 10.1038/ismej.2016.86
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of ecological rescue for altered soil microbial communities and functions

Abstract: Soil ecosystems worldwide are subjected to marked modifications caused by anthropogenic disturbances and global climate change, resulting in microbial diversity loss and alteration of ecosystem functions. Despite the paucity of studies, restoration ecology provides an appropriate framework for testing the potential of manipulating soil microbial communities for the recovery of ecosystem functioning. We used a reciprocal transplant design in experimentally altered microbial communities to investigate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
82
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(104 citation statements)
references
References 54 publications
8
82
0
3
Order By: Relevance
“…The microbiota in ENB showed low OTU richness as well as low diversity, as compared with soil environmental samples (Tan et al ., ; Calderón et al ., ), composts (Wang et al ., ), water (Thaler et al ., ) and guts (Griffin et al ., ). It means that the decaying ENB hosted a microbiota of limited complexity, comparable to that of seed endophytic microbiota (Barret et al ., ), with a similar feature that their relative abundances of microbial taxa were quite uneven.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiota in ENB showed low OTU richness as well as low diversity, as compared with soil environmental samples (Tan et al ., ; Calderón et al ., ), composts (Wang et al ., ), water (Thaler et al ., ) and guts (Griffin et al ., ). It means that the decaying ENB hosted a microbiota of limited complexity, comparable to that of seed endophytic microbiota (Barret et al ., ), with a similar feature that their relative abundances of microbial taxa were quite uneven.…”
Section: Discussionmentioning
confidence: 99%
“…The resource‐based niche theory associates the establishment of potential invaders with local resource availabilities and the ecological traits of resident species (Tilman, ). These results also provide evidence for a habitat filtering process, that is, the nonrandom establishment and colonization of individuals with respect to abiotic local characteristics, and this would suggest that the microbial communities were assembled via deterministic rather than stochastic processes (Calderon et al, ; Placella et al, ).…”
Section: Discussionmentioning
confidence: 72%
“…Currently, there are a growing number of studies investigating the temporal dynamics of microbial communities in response to environmental contamination, defined as microbial succession (Fierer, Nemergut, Knight, & Craine, ; Jiao, Chen, et al, ; Jiao, Liu, et al, ). Yet we still lack basic knowledge of how microbial species interact and idiosyncratic effects influence biodiversity and ecosystem functioning during microbial community succession with one or more introduced microbial consortia (Calderon et al, ; Harris, ; Laughlin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments showing reciprocal soil inoculation or soil transplantation capable of surmounting disease in wheat (Henry, 1931), restore degraded land and giving direction to the type of vegetation grown based on soil inocula (Wubs et al, 2016) and degrade crude oil (Bell et al, 2016) lend credence to the first approach. The work of Calderon et al (2016) on the restoration of the microbial communities responsible for N-cycling in degraded soil using reciprocal soil inoculum suggests that having an understanding of the priority effects along with the relatedness of the established microbial community and the introduced microbial communities could help in better microbial assemblage and successful restoration of target areas. In a recent work of Bai et al (2015), it has been shown that, with some meticulous, systematic and exhaustive isolation of bacteria from phyllosphere and rhizosphere, it is possible to capture majority of the species found reproducibly in their respective natural communities.…”
Section: Co-propagating the Co-evolvedmentioning
confidence: 99%